Pengembangan E-modul berbasis Augmented Reality (AR) pada Materi Sistem Pernapasan Manusia Kelas XI SMAN 9 Makassar - Ainun Mardia; Nurul Magfirah; Rahmatia Thahir (Mataram University, 2026)
This study aims to develop an Augmented Reality (AR)-based e-module on the human respiratory system material for eleventh-grade students at SMAN 9 Makassar. This study employed the Research and Development (R&D) method using the ADDIE development model, which consists of analysis, design, development, implementation, and evaluation stages. The research instruments included validation sheets, teacher and student response questionnaires, and learning outcome tests. The results showed that the AR-based e-module obtained a validity score of 0.96, which was categorized as very valid. The practicality level based on the teacher responses reached 96.25%, while the student responses reached 81.25%, both categorized as very practical. Furthermore, the effectiveness analysis using the N-gain test obtained an average score of 0.43, which was categorized as moderate. Based on these findings, the AR-based e-module was declared valid, practical, and sufficiently effective for use in Biology learning on the topic of the human respiratory system.